Synthesis and Characterization of Fluoridated Silver Nanoparticles and Their Potential as a Non-Staining Anti-Caries Agent - Yin IX (Dove Medical Press, 2020)
Iris Xiaoxue Yin,1,2 Irene Shuping Zhao,3 May Lei Mei,4 Edward Chin Man Lo,1 Jinyao Tang,5 Quanli Li,6 Lok Yan So,7 Chun Hung Chu1,2 1Faculty of Dentistry, The University of Hong Kong, Hong Kong, People’s Republic of China; 2HKU Shenzhen Institute of Research and Innovation, Shenzhen, People’s Republic of China; 3School of Dentistry, Shenzhen University Health Science Center, Shenzhen, People’s Republic of China; 4Faculty of Dentistry, University of Otago, Dunedin, New Zealand; 5Department of Chemistry, The University of Hong Kong, Hong Kong, People’s Republic of China; 6School of Stomatology, Anhui Medical University, Hefei, People’s Republic of China; 7Department of Applied Biology and Chemical Technology, The Hong Kong Polytechnic University, Hong Kong, People’s Republic of ChinaCorrespondence: May Lei MeiDepartment of Oral Rehabilitation, Faculty of Dentistry, University of Otago, Dunedin, New ZealandTel +64 3 479 4196Fax +64 3 479 5079Email may.mei@otago.ac.nzChun Hung ChuFaculty of Dentistry, The University of Hong Kong, 34 Hospital Road, Hong Kong SAR, People’s Republic of China Tel +852 2859 0287Fax +852 2858 2532Email chchu@hku.hkObjectives: The first objective of this study was to prepare sodium fluoride (NaF) solution with various concentrations of polyethylene glycol-coated silver nanoparticles (PEG-AgNPs). The second objective was to study the antibacterial activity against Streptococcus mutans and the tooth-staining effect of the solution.Methods: PEG-AgNPs were prepared via the one-step chemical reduction of silver acetate with thiolated polyethylene glycol. The PEG-AgNPs were characterized with ultraviolet-visible spectrometry and transmission electron microscopy. The half maximal inhibitory concentration (IC50) for the PEG-AgNPs against Streptococcus mutans and human gingival fibroblasts (HGF-1) were determined. The staining effect on dentin and enamel for the 2.5% NaF solutions with PEG-AgNPs at 12,800, 6400, 1600, and 400 ppm was investigated using digital spectrophotometry. The IC50 of the fluoridated silver nanoparticles against Streptococcus mutans were measured.Results: The PEG-AgNPs have an average diameter of 2.56± 0.43 nm and showed excellent stability at high ionic strength (2.5% NaF) for 18 months. The IC50 of PEG-AgNPs against Streptococcus mutans was found to be 21.16± 1.08 ppm silver, which was half of IC50 against HGF-1 cells (42.36± 1.12 ppm), providing a working range to kill bacteria with no harm to human cells. The formulations with different concentrations of PEG-AgNPs showed no significant staining of teeth. Combining PEG-AgNPs with NaF significantly expanded the therapeutic window against Streptococcus mutans by reducing its IC50.Conclusion: A biocompatible solution of NaF with PEG-AgNPs was developed. Because it has antibacterial activity against Streptococcus mutans and no tooth-staining effect, it can be used as an anti-caries agent.Keywords: silver, nanoparticles, fluoride, dentin, caries, antibacterial